Preparation of CaO-SiO2 adsorbent for potential CO2 capture via dry mixing method - Mohd Daud, Farah Diana; Kosen, Nur Asyikin; Mahmud, Mudrikah Sofia; Sarifuddin, Norshahida; Mohd Zaki, Hafizah Hanim (Trans Tech Publications Ltd, Switzerland, 2021)
Calcium-looping technology is defined as one of the most desirable methods of carbon capture, utilization and storage (CCUS). However, because of sintering, rapid deactivation of CaOsorbents is currently a major barrier to this technology. The stability of calcium based sorbent may be enhance by incorporating them with inert support materials such as MgO, Al2O2, ZrO2 and SiO2. For this study, calcium based sorbent has been incorporate with silica obtained from rice husk ash. CaO-SiO2 sorbents are prepared using physical dry mixing method which is much simpler compared to other available methods. The prepared CaO-SiO2 sorbents were then characterized using scanning electron microscopy (SEM) and X-ray diffraction (XRD). New crystalline phase, larnite (Ca2SiO4) was detected in XRD patterns and this phase possess good chemical durability and may help to prevent sintering effect of calcium based sorbents and enhance their cyclic capability. CaO-SiO2 sorbent calcined at 700 ºC with different grinding times have highest intensity of XRD peak at (104) with element of calcite. Sorbents with different weight composition of CaCO3-RHA were observed to have different surface morphology. SEM images of the sorbent (90wt% CaCO3-RHA) before calcination showed bigger particle size with irregular shape and more porosity. Then, SEM analysis was conducted for samples with different grinding times after calcination. CaO-SiO2 sorbents with 20minutes grinding time exhibited small size of particles with some porosity. Besides that, the particles are well distributed without agglomeration occured. The CaO-SiO2 sorbent calcined at 700 ºC sorbents were tested for 20 consecutive carbonation and calcination cycles using Thermogravimetric Analysis (TGA). CaO-SiO2 sorbent treated with 700 ºC calcination temperature and 20 minutes of grinding shows better cyclic CO2 sorption capacity.